Serum 25-Hydroxyvitamin D is inversely associated with Nasopharyngeal carcinoma: a hospital-based matched case–control study in Malaysia - Ulaganathan, Vaidehi; Lye, Munn Sann; Loh, Su Peng; Yap, Yoke Yeow; Kandiah, Mirnalini; Augundhooa, Digsha; Bhattacharya, Tanima; Al-Olayan, Ebtesam; Wang, Chuanyi (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
Serum 25(OH)D deficiency consistently demonstrated molecular mechanisms through which chronic inflammation is associated with the risk of nasopharyngeal carcinoma (NPC). This study aimed to determine the association between serum 25(OH)D and NPC. A matched case–control study was conducted at two local hospitals. A total of 300 histologically confirmed NPC cases were matched with controls for age, gender, and ethnicity, and assessed for vitamin D status and other nutritional factors. Mean Vitamin D concentration was significantly lower among cases compared to controls (63.17 ± 19.15 nmol/L and 67.34 ± 23.06 nmol/L) (t = −2.41, p = 0.016). Multiple conditional logistic regression analysis indicated that higher levels of serum 25(OH)D were associated with reduced odds of NPC (AOR = 0.73, 95 CI = 0.57–0.94, p = 0.016) controlling for confounders including BMI, physical activity, smoking status, alcohol consumption, consumption of food high in vitamin D, salted fish consumption, and family history of NPC. There was a significant association between inadequate serum 25(OH)D status with accumulation of four risk factors and increased odds of getting NPC using polynomial regression analysis. Increased NPC odds ratios were observed after sequential accumulation of additional risk factors with the presence of inadequate serum 25(OH)D status (OR = 0.54, 95 CI = 0.27, 4.77, p = 0.322, OR = 1.04, 95 CI = 0.64, 1.72, p = 0.267, OR = 1.15, 95 CI = 0.73, 1.80, p = 0.067, OR = 1.93, 95 CI = 1.13, 3.31, p = 0.022, and OR = 5.55, 95 CI = 1.67, 10.3, p < 0.001 respectively). Future research in Malaysia should involve both prospective cohort studies and randomized controlled trials to confirm and further clarify the role of vitamin D in NPC outcomes.